DEVELOPING INK’S KIT MEDIA TO STUDY SPEAKING SKILLS IN DESCRIPTIVE TEXT FOR THE SEVENTH GRADE JUNIOR HIGH SCHOOL - Inka Paradita Fitriani; Nita Sutanti; Yusniarsi (Universitas Islam Balitar, 2023)
English is one of the subjects taught to students since elementary school. In this study, researchers conducted research on seventh grade junior high school students. The problems found are low speaking skills and students need improvement in English learning media. Researchers conducted research focused on speaking skills in descriptive text material. Researchers use flashcards media that are processed and updated in use during learning, which are packaged in one ink's Kit media package. The purpose of this study was to develop flashcards to teach speaking skills to seventh grade junior high school students. The researcher used simple random sampling. The subjects of this study were students of SMPN 2 Doko Class VII D as many as 35 students and 2 teachers. The data analysis technique used was qualitative and quantitative. Qualitative data were taken from observations, interviews, and documentation. Quantitative data is taken from the perception test. From the results of the perception test, it was found that the product was feasible to be used for learning students' speaking skills. Based on the Likert Scale in the perception test, it was found that 88.75% of students' perceptions with information strongly agree on the use of the product as a medium for learning English in descriptive text material. The results of the teacher's perception of the use of the developed product strongly agree that is equal to 85.3%. The results of the material validation assessment on the product were found to be 88.2% with information very suitable for use in learning. The results of the media validation assessment were found to be 81.1% with information very suitable for use in learning. The result of the research that by playing INK’s Kit Media can be used to improve their speaking skill.